Investigation of wet spraying system to control dust pollution in mines (A case study ) - Mahmoud Makkiabadi; Sara Yaghoobi; Mohammad Saleh Haj Mohammadi (Anthropogenic Pollution)
Industrial dust has a significant effect on the environment of mines, which leads to an increase in illness among workers. To decrease the impact of dust on the climate, a wet spraying system is useful for controlling dust in mining companies. In this paper, by using the wet (water) spraying system, dust control in the area of the crusher and pellet plant (discharge tower) has been investigated by Goharzamin Iron Ore company. Goharzamin Iron Ore company has an essential role producing of steel in Iran. There are a 15 million tons gyratory crusher, three iron concentrate plants with an annual capacity of 6 million tons, and a pelletizing plant with annual capacity of 5 million tons. The dust was controlled in the gyratory crusher area of Goharzamin Iron Ore company by using a wetting spraying system. Results showed that the rates of PM10 for the east, west, north and south sides of the gyratory crusher and also the center of this system are equal 851.2, 647.5, 643.9 and 781.2, and 1116.3 Î¼g/m3, respectively. Foremore, after turning on the wet spraying system in this area, these values are reduced to 128.3, 112.8, 115.9, 123.7, and 189.9 Î¼g/m3, respectively. The results showed that the water spray system in the gyratory crusher area reduced the PM2.5 (Particulate matter) and PM10 particles by 67% and 80%, respectively.